XV. The Impact of the Digital Economy on Logistics and Supply Chain Management Under the “Belt and Road” Initiative - Lang, Shusen; Zhu, Enyang (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
This paper explores the impact of the digital economy on logistics and supply chain management in countries participating in the Belt and Road Initiative (BRI). It highlights how digital technologies—such as big data, AI, IoT, and blockchain—enhance efficiency, improve risk management, and support sustainable development across international logistics networks. The study also identifies significant challenges, including infrastructure gaps, customs inefficiencies, and digital disparities. Through a comprehensive analysis, it proposes digital strategies to optimise logistics performance and strengthen cooperation among BRI countries. The findings emphasise the transformative role of the digital economy in facilitating cross-border trade, reducing costs, and fostering integration in global supply chains.